A Retrospect of Energy Demand and Potential of Sub-Saharan Africa: Leveraging Energy Deficit to Attain Clean Energy Hub Region - Ebhota, W. S.; Tabakov, P. Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The lack of reliable energy access is a significant obstacle to the socio-economic progress of the Global South, particularly sub-Saharan Africa (SSA). This research explores the current energy demand and access situation, evaluated SSA's renewable energy (RE) potential, identifies barriers to RE development, and proposed strategies to overcome these challenges. The study emphasises the importance of establishing RE infrastructure for a sustainable energy transition and outlined necessary investments. With an impressive 11,000 gigawatts (GW) of exploitable generating capacity, RE has the potential to replace fossil fuels effectively in SSA. The dominant resources are solar (10 TW), hydro (350 GW), wind (110 GW), and geothermal (15 GW) energy. Challenges include high initial costs, limited financing access, grid integration issues, infrastructure deficiencies, regulatory frameworks, and resource variability. To address these challenges, the study suggests policy and regulatory reforms, expanded financing access, capacity building, and improved grid infrastructure. Overall, this research presents the energy deficit and RE potential in SSA as opportunities for the region to become a clean energy hub, requiring collaboration among governments, academic institutions, industry stakeholders, and international organizations.